2009
DOI: 10.1111/j.1600-0560.2009.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of p53, cyclinD1 and histopathological features in basal cell carcinomas

Abstract: P53 expression seems to be related to Ki67 index and some histopathological features of BCC, such as infiltrative histological growth pattern and probably fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
2
5
1
Order By: Relevance
“…Previous studies have found p53 expression in cutaneous neoplasms to vary between 42% and 84% (17,18). In our study, the expression was found to be 81.8%.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have found p53 expression in cutaneous neoplasms to vary between 42% and 84% (17,18). In our study, the expression was found to be 81.8%.…”
Section: Discussionsupporting
confidence: 65%
“…BCCs that occur in sun‐exposed sites more frequently show p53 overexpression than do those in less‐exposed areas . Aggressive BCCs, especially infiltrative and basosquamous subtypes, have higher rates of p53 positivity and higher mean Ki‐67 index values . However, in our study, overexpression of the p53 protein was more commonly observed in genital BCCs, of which 85% belonged to nodular or superficial types.…”
Section: Discussioncontrasting
confidence: 64%
“…Epidermal p53 clones are clusters of morphologically normal keratinocytes with intense nuclear accumulation of immunoreactive p53 . Such p53 clones are frequently found in chronically sun‐exposed skin, and the mutations of epidermal p53 clones are mostly missense and represent the typical UV signature .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of RAR was almost significantly lower in BCCs than in control tissues (p=0.056). The expression of the www.intechopen.com (100,106,107,158,161) and by the apoptotic index (124). The markers Ki-67 and p53 can impart supplementary information and are important for histopathological diagnosis with regard to making a clinical judgement of the consequences of "tumor-free margin".…”
Section: Biomarkers For Chemoprevention Of Basal Cell Carcinomasmentioning
confidence: 99%